PPS composite material with low dielectric loss and low water absorption, preparation method and application thereof

CN122958864APending Publication Date: 2026-10-23SHENZHEN JIAKAILE IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611236267.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而该技术方案的未关注介电损耗和抗冲击性

Benefits of technology

1、本发明创造性采用氨基-四聚乙二醇-羧酸对氨基化六方氮化硼进行插层后接枝多官能环氧缩水甘油醚,一方面提高六方氮化硼的分散性,有助于六方氮化硼形成导热网络,另一方面,提高了六方氮化硼与PPS树脂基体间的界面作用,降低PPS复合材料的介电常数和介电损耗,而且也可以在一定程度上改善PPS的力学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application belongs to the technical field of PPS composite materials, and particularly relates to a PPS composite material with low dielectric loss and low water absorption, a preparation method and application thereof. The PPS composite material comprises the following components in parts by mass: PPS resin 50-70 parts, modified hexagonal boron nitride 25-35 parts, modified composite whisker 10-20 parts, antioxidant 0.5-2 parts, and lubricant 0.5-1 part. The modified hexagonal boron nitride is obtained by grafting multifunctional epoxy glycidyl ether on the amino-tetrapolyethylene glycol-carboxylic acid intercalated hexagonal boron nitride. The modified composite whisker is a calcium sulfate whisker and an alumina whisker coated by a double-end amino liquid butyronitrile rubber. The PPS composite material provided by the application solves the technical problems of high thermal conductivity, high dielectric and insufficient toughness of conventional PPS composite materials, has the characteristics of low water absorption, and can be applied as a substrate material of a high-frequency circuit in the field of electronic appliances.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of PPS composite material technology, specifically relating to a PPS composite material with low dielectric loss and low water absorption, its preparation method, and its application. Background Technology

[0002] Polyphenylene sulfide (PPS) is a thermoplastic engineering plastic containing phenyl sulfide groups in its molecular backbone. It has excellent thermal stability, chemical stability and electrical insulation properties, and has broad application prospects as a substrate material for high-frequency circuits in the field of electronics and electrical appliances.

[0003] However, while PPS maintains relatively stable dielectric constant and dielectric loss over a wide frequency range, it suffers from poor dielectric properties and insufficient thermal conductivity at high frequencies (5G / 6G). Furthermore, due to the low relative molecular mass of PPS, coupled with the increased rigidity of the polymer chain caused by the numerous benzene rings in the PPS main chain, it exhibits low brittleness and impact toughness.

[0004] To address the aforementioned technical problems, Chinese Patent CN121895760A discloses a polyphenylene sulfide (PPS) composite material with low dielectric constant and low dielectric loss, comprising the following components by mass: 100 parts PPS resin, 5-50 parts microencapsulated filler, 5-30 parts reinforcing fiber, 0.5-5 parts surface modifier, and 0.1-3 parts dispersant; the total amount of microencapsulated filler and reinforcing fiber does not exceed 65 parts. The microencapsulated filler is made by encapsulating a low-dielectric filler within a low-dielectric-constant polymer shell. This technical solution employs microencapsulation technology, encapsulating the low-dielectric filler within a polymer shell with a low dielectric constant, and then composites it with a PPS matrix. The microencapsulated filler can reduce the direct contact between the filler and the PPS matrix, thereby reducing interfacial polarization and dielectric loss. However, this technical solution does not address its thermal conductivity and impact resistance.

[0005] Chinese patent CN121045827B discloses a high thermal conductivity polyphenylene sulfide (PPS) composite material, comprising: an insulating and thermally conductive filler, PPS resin, an epoxy-containing silane coupling agent, and a block copolymer. This technical solution designs and synthesizes a block copolymer compatibilizer, introducing polar urea bonds into the middle of the molecular chain, and introducing trifluoromethyl and phosphoro-phenanthroline structures into the compatibilizer through the amino groups at both ends. This improves the bonding effect between the compatibilizer and the insulating and thermally conductive filler and the PPS resin matrix, while simultaneously enhancing the flame retardancy and hydrophobicity of the composite material. Furthermore, the compatibilizer can form an effective heat conduction pathway, reduce the agglomeration of hexagonal boron nitride filler, and fill interfacial voids between the filler and the PPS resin matrix, thereby improving the composite material's thermal conductivity, processability, mechanical properties, and reducing its dielectric constant. However, this technical solution does not address dielectric loss and impact resistance. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a PPS composite material with low dielectric loss and low water absorption, as well as its preparation method and application.

[0007] To achieve the above objectives, the present invention provides the following technical solution: The first aspect of the present invention provides a PPS composite material with low dielectric loss and low water absorption, comprising the following components by mass: 50-70 parts of PPS resin, 25-35 parts of modified hexagonal boron nitride, 10-20 parts of modified composite whiskers, 0.5-2 parts of antioxidant, and 0.5-1 parts of lubricant.

[0008] There are no special requirements for the specific selection of the PPS resin in this invention; conventional linear PPS resin in the art can be selected.

[0009] In a preferred embodiment of the present invention, the modified hexagonal boron nitride is formed by intercalating hexagonal boron nitride with amino-tetraethylene glycol-carboxylic acid and then grafting multifunctional epoxy glycidyl ether.

[0010] Further, the preparation method of the modified hexagonal boron nitride is as follows: aminated hexagonal boron nitride, amino-tetraethylene glycol-carboxylic acid and water are mixed, ultrasonically dispersed, heated and stirred, centrifuged, washed and dried to obtain amino-tetraethylene glycol-carboxylic acid intercalated hexagonal boron nitride; The amino-tetraethylene glycol-carboxylic acid intercalated hexagonal boron nitride, multifunctional epoxy glycidyl ether, and ethanol are mixed, heated and stirred, centrifuged, washed, and dried to obtain the final product.

[0011] Boron nitride (BN) possesses excellent dielectric and thermal conductivity properties and has been widely used in PPS composites. However, existing technologies often employ a large amount of BN, typically comparable to the amount of PPS resin used. This results in poor dispersion of BN in the system, affecting the mechanical properties of the PPS composite. Simultaneously, the interfacial compatibility between BN and PPS is poor. While a large amount of BN can improve thermal conductivity, it also leads to charge accumulation at the interface, increasing the dielectric constant and dielectric loss, making it impossible to obtain low-dielectric-performance PPS composites suitable for 5G applications.

[0012] To solve this technical problem, this invention creatively employs an amino-tetraethylene glycol-carboxylic acid to intercalate aminated hexagonal boron nitride followed by grafting of multifunctional epoxy glycidyl ether. Specifically, under the action of a mixed acid and potassium permanganate, hydroxyl and amino groups are introduced at the edges and defects of the boron nitride layer, opening up the interlayer space of the boron nitride. The carboxylic acid groups in the amino-tetraethylene glycol-carboxylic acid can react with the amino groups on the hexagonal boron nitride. Inserting the amino-tetraethylene glycol-carboxylic acid into the interlayer space of the boron nitride improves the dispersion of the hexagonal boron nitride. The amino groups on the surface and between the layers of hexagonal boron nitride (PBN) can undergo ring-opening reactions with the epoxy groups in the polyfunctional epoxy glycidyl ether, thus grafting polyfunctional epoxy glycidyl ether onto the surface and between the layers of PBN. This grafting not only improves the interfacial interaction between PBN and the PPS resin matrix, reducing the dielectric constant and dielectric loss of the PPS composite material, but its flexible segments can also improve the mechanical properties of PPS to some extent.

[0013] Furthermore, the mass ratio of the aminated hexagonal boron nitride, amino-tetraethylene glycol-carboxylic acid, and water is 1:0.7-0.9:40-60.

[0014] Furthermore, the mass ratio of the amino-tetraethylene glycol-carboxylic acid intercalated hexagonal boron nitride, the multifunctional epoxy glycidyl ether, and ethanol is 10-15:2-3:200-250.

[0015] The preparation method of the aminated hexagonal boron nitride described in this invention refers to the method disclosed in Chinese Patent No. CN121108827B. Specifically, hexagonal boron nitride is added to a mixture of concentrated sulfuric acid and concentrated phosphoric acid in a volume ratio of 2:1, stirred at 0-5°C, and potassium permanganate is added. The temperature is then raised to 30-35°C, and the reaction is allowed to proceed for 8-12 hours. Hydrogen peroxide is added to the reaction solution at 0-1°C until the purple color of the reaction solution fades. The solution is then centrifuged, filtered, and washed to obtain the final product.

[0016] Furthermore, the particle size of the hexagonal boron nitride is 0.5-1µm.

[0017] Furthermore, the mass ratio of the hexagonal boron nitride, potassium permanganate, and mixed acid is 1:2-3:70-80.

[0018] Furthermore, the multifunctional epoxy glycidyl ether is selected from at least one of glycerol triglycidyl ether, trimethylolpropane triglycidyl ether, and trimethylolethane triglycidyl ether.

[0019] In an embodiment of the present invention, the modified hexagonal boron nitride is prepared by mixing amino-modified hexagonal boron nitride, amino-tetraethylene glycol-carboxylic acid and water, ultrasonically dispersing, stirring continuously at 60-70°C for 8-12 hours, centrifuging, washing and drying to obtain amino-tetraethylene glycol-carboxylic acid intercalated hexagonal boron nitride. The amino-tetraethylene glycol-carboxylic acid intercalated hexagonal boron nitride, multifunctional epoxy glycidyl ether, and ethanol are mixed and stirred at 60-80℃ for 5-8 hours. After centrifugation, washing, and drying, the product is obtained.

[0020] In a preferred embodiment of the present invention, the modified composite whiskers are calcium sulfate whiskers and alumina whiskers coated with double-terminated amino liquid nitrile rubber.

[0021] Furthermore, the modified composite whiskers are prepared by mixing calcium sulfate whiskers, alumina whiskers, double-terminated amino liquid nitrile rubber and acetone, heating and stirring, filtering and drying to obtain the product.

[0022] Furthermore, the calcium sulfate whiskers are columnar fibrous in shape.

[0023] Furthermore, the diameter of the calcium sulfate whiskers is ≤10µm and the length is ≤50µm.

[0024] Furthermore, the diameter of the alumina whiskers is ≤1µm and the length is ≤10µm.

[0025] Furthermore, the number-average molecular weight of the dual-amino-terminated liquid nitrile rubber is 2000-5000.

[0026] Furthermore, the mass ratio of the calcium sulfate whiskers, alumina whiskers, double-terminated amino liquid nitrile rubber, and acetone is 1:2-4:0.3-0.5:10-15.

[0027] On its own, modifying composite whiskers with double-amino-terminated liquid nitrile rubber does not offer significant advantages and is a conventional modification method used in the field to improve the toughness of PPS composites. However, another important function of the modified composite whiskers of this invention lies in their progressive combination with modified hexagonal boron nitride, which significantly improves the dielectric and thermal conductivity of PPS composites. Specifically, the amino groups at one end of the double-amino-terminated liquid nitrile rubber molecular chain can be anchored to the surface of the composite whiskers, while the amino groups at the other end undergo a ring-opening chemical reaction with the epoxy groups remaining on the surface of the modified hexagonal boron nitride. This allows the composite whiskers to bridge the hexagonal boron nitride, and the two work together to construct a more complete, continuous, and efficient thermal conductivity network. At the same time, this further eliminates the voids and defects at the interface between hexagonal boron nitride, composite whiskers, and PPS resin, thereby significantly improving the dielectric and thermal conductivity of PPS composites.

[0028] In particular, the inventors unexpectedly discovered during the experiment that only when calcium sulfate whiskers and alumina whiskers with specific physical properties and at a specific mass ratio can the modified composite whiskers achieve excellent synergistic effects with modified hexagonal boron nitride.

[0029] In one embodiment of the present invention, the modified composite whiskers are prepared by mixing calcium sulfate whiskers, alumina whiskers, double-terminated amino liquid nitrile rubber and acetone, stirring at 30-50°C for 2-4 hours, filtering and drying to obtain the product.

[0030] The present invention does not impose specific limitations on the selection of antioxidants. Any type of antioxidant conventional in the art can be selected. For example, the antioxidants include at least one of hindered amine antioxidants, hindered phenolic antioxidants, phosphite antioxidants and thioester antioxidants.

[0031] For example, the antioxidants include, but are not limited to, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (antioxidant 1010), octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (antioxidant 1076), triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate] (antioxidant 245), tris(2,4-di-tert-butylphenyl) phosphite (antioxidant 168), and bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphate (PEP36), etc.

[0032] The present invention does not impose specific limitations on the selection of the lubricant; any type of lubricant conventional in the art may be selected. For example, the lubricant includes at least one of ester lubricants, alcohol lubricants, hydrocarbon lubricants, fatty acid lubricants, fatty acid amide lubricants, and metal soap lubricants.

[0033] For example, the lubricant includes, but is not limited to, vinyl bis-stearamide, erucamide, stearate, polyethylene wax, etc.

[0034] The second aspect of the present invention provides a method for preparing a PPS composite material with low dielectric loss and low water absorption, comprising the following steps: mixing PPS resin, modified hexagonal boron nitride, modified composite whiskers, antioxidant and lubricant, and feeding the mixture into a twin-screw extruder for extrusion granulation to obtain the composite material.

[0035] The third aspect of this invention provides the application of a PPS composite material with low dielectric loss and low water absorption rate as a substrate material for high-frequency circuits in the field of electronics and electrical appliances.

[0036] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows: 1. This invention creatively employs amino-tetraethylene glycol-carboxylic acid to intercalate aminated hexagonal boron nitride and then graft multifunctional epoxy glycidyl ether. On the one hand, this improves the dispersibility of hexagonal boron nitride, which helps it form a thermally conductive network. On the other hand, it enhances the interfacial interaction between hexagonal boron nitride and the PPS resin matrix, reduces the dielectric constant and dielectric loss of the PPS composite material, and can also improve the mechanical properties of PPS to a certain extent.

[0037] 2. This invention uses double-terminated amino liquid nitrile rubber to modify calcium sulfate whiskers and alumina whiskers with specific physical properties at a specific mass ratio. This not only improves the toughness of PPS composite materials, but also works synergistically with modified hexagonal boron nitride to significantly improve the dielectric and thermal conductivity of PPS composite materials.

[0038] 3. The PPS composite material provided by this invention has a dielectric constant <3.5, dielectric loss <0.003, thermal conductivity >3.8 W / (m·K), and cantilever beam notched impact strength >14 kJ / m at a frequency of 10 GHz. 2 With a tensile strength >150MPa, it solves the technical problems of high thermal conductivity, high dielectric constant, and insufficient toughness of conventional PPS composite materials. At the same time, PPS resin has the characteristic of low water absorption, which enables it to be used as a substrate material for high-frequency circuits in the field of electronics and electrical appliances. Detailed Implementation

[0039] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0040] Unless otherwise specified in the examples and comparative examples, the conditions were performed under standard conditions or conditions recommended by the manufacturer. All reagents and instruments used were commercially available products unless otherwise specified.

[0041] Exemplary sources of some of the raw materials in the following embodiments and comparative examples: (1) The PPS resin is linear PPS resin, Chengdu Letian Plastics Co., Ltd., model: PL002.

[0042] (2) The preparation method of aminated hexagonal boron nitride is as follows: add hexagonal boron nitride to a mixture of concentrated sulfuric acid and concentrated phosphoric acid with a volume ratio of 2:1, stir at 5°C, add potassium permanganate, then heat to 30°C and react for 10 hours; at 0°C, add hydrogen peroxide to the reaction solution until the purple color of the reaction solution fades, centrifuge, filter, and wash to obtain the product.

[0043] The mass ratio of the hexagonal boron nitride, potassium permanganate, and mixed acid is 1:3:80.

[0044] (3) The particle size of hexagonal boron nitride is 1µm, Liaoning Borda Technology Co., Ltd.

[0045] (4) Amino-tetraethylene glycol-carboxylic acid: CAS No.: 663921-15-1.

[0046] (5) The particles of calcium sulfate whiskers A are columnar fibers with a diameter of 1-10µm and a length of 10-100µm. Shanghai Fengzhu Composite New Materials Technology Co., Ltd., model: NP-S04-S.

[0047] Calcium sulfate whiskers B have columnar fiber shapes with diameters of 1-15µm and lengths of 10-300µm. (Shanghai Fengzhu Composite New Materials Technology Co., Ltd., Model: NP-HF03)

[0048] Calcium sulfate whiskers C have needle-like fiber shapes, with a diameter of 1-20µm and a length of 10-200µm. (Shanghai Fengzhu Composite New Materials Technology Co., Ltd., Model: NP-M02)

[0049] Calcium sulfate whiskers D have needle-like fiber shapes, with a diameter of 1-4µm and a length of 10-300µm. (Locke Chemical, model: NP-M02)

[0050] (6) The diameter of the alumina whiskers is 300 nm and the length is 5.5 ± 0.5 µm, HSBC Nano.

[0051] (7) The number average molecular weight of the double-terminated amino liquid nitrile rubber is 3500±500, the amine value is 1.3±0.3, Kunshan Castel Polymer Materials Co., Ltd., model: ATBN-II.

[0052] Example 1: A PPS composite material with low dielectric loss and low water absorption rate, which is composed of the following components by mass: 50 parts PPS resin, 25 parts modified hexagonal boron nitride, 10 parts modified composite whiskers, 0.5 parts antioxidant, and 0.5 parts lubricant.

[0053] The modified hexagonal boron nitride is prepared by mixing amino-modified hexagonal boron nitride, amino-tetraethylene glycol-carboxylic acid and water, ultrasonically dispersing, stirring continuously at 65°C for 10 hours, centrifuging, washing and drying to obtain amino-tetraethylene glycol-carboxylic acid intercalated hexagonal boron nitride. The amino-tetraethylene glycol-carboxylic acid intercalated hexagonal boron nitride, multifunctional epoxy glycidyl ether (glycerol triglycidyl ether), and ethanol were mixed and reacted at 70°C for 6 hours. The mixture was then centrifuged, washed, and dried to obtain the final product.

[0054] The mass ratio of the aminated hexagonal boron nitride, amino-tetraethylene glycol-carboxylic acid, and water is 1:08:50.

[0055] The mass ratio of the amino-tetraethylene glycol-carboxylic acid intercalated hexagonal boron nitride, the multifunctional epoxy glycidyl ether, and ethanol is 12:3:250.

[0056] The modified composite whiskers are prepared by mixing calcium sulfate whiskers A, alumina whiskers, double-terminated amino liquid nitrile rubber and acetone, stirring at 40°C for 3 hours, filtering and drying to obtain the final product.

[0057] The mass ratio of the calcium sulfate whiskers A, alumina whiskers, double-terminated amino liquid nitrile rubber, and acetone is 1:3:0.4:12.

[0058] The antioxidants are antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1.

[0059] The lubricant is vinyl bis-stearamide.

[0060] The preparation method of the above-mentioned PPS composite material with low dielectric loss and low water absorption includes the following steps: mixing PPS resin, modified hexagonal boron nitride, modified composite whiskers, antioxidant and lubricant, and feeding them into a twin-screw extruder for extrusion granulation to obtain the composite material.

[0061] Example 2 The only difference from Example 2 is that the PPS composite material with low dielectric loss and low water absorption rate is composed of the following components by mass: 60 parts PPS resin, 30 parts modified hexagonal boron nitride, 15 parts modified composite whiskers, 1 part antioxidant, and 0.8 parts lubricant; all other components are the same.

[0062] Example 3 The only difference from Example 2 is that the PPS composite material with low dielectric loss and low water absorption rate is composed of the following components by mass: 70 parts PPS resin, 35 parts modified hexagonal boron nitride, 20 parts modified composite whiskers, 1.8 parts antioxidant, and 1 part lubricant; all other components are the same.

[0063] Example 4 The only difference from Example 2 is that calcium sulfate whisker A is replaced with calcium sulfate whisker B; everything else is the same.

[0064] Example 5 The only difference from Example 2 is that calcium sulfate whisker A is replaced with calcium sulfate whisker C; everything else is the same.

[0065] Example 6 The only difference from Example 2 is that calcium sulfate whisker A is replaced with calcium sulfate whisker D; everything else is the same.

[0066] Example 7 The only difference from Example 2 is that the mass ratio of calcium sulfate whiskers A, alumina whiskers, double-terminated amino liquid nitrile rubber and acetone is 1:5:0.4:15; all other aspects are the same.

[0067] Example 8 The only difference from Example 2 is that the mass ratio of calcium sulfate whiskers A, alumina whiskers, double-terminated amino liquid nitrile rubber and acetone is 1:1:0.3:12; all other aspects are the same.

[0068] Comparative Example 1 The only difference from Example 2 is that the modified hexagonal boron nitride is prepared by mixing aminated hexagonal boron nitride, amino-tetraethylene glycol-carboxylic acid and water, ultrasonically dispersing, stirring continuously at 65°C for 10 hours, centrifuging, washing and drying to obtain the product; the rest are the same.

[0069] Comparative Example 2 The only difference from Example 2 is that the modified hexagonal boron nitride is prepared by mixing aminated hexagonal boron nitride, multifunctional epoxy glycidyl ether (glycerol triglycidyl ether) and ethanol, stirring and reacting at 70°C for 6 hours, centrifuging, washing, and drying to obtain the product.

[0070] The mass ratio of the aminated hexagonal boron nitride, the polyfunctional epoxy glycidyl ether, and ethanol is 12:3:250; all other components are the same.

[0071] Comparative Example 3 The only difference from Example 2 is that the low dielectric loss and low water absorption PPS composite material, by mass, consists of the following components: 60 parts PPS resin, 30 parts hexagonal boron nitride, 0.6 parts silane coupling agent KH560, 15 parts modified composite whiskers, 1 part antioxidant, and 0.8 parts lubricant. The preparation method of the above-mentioned low dielectric loss and low water absorption PPS composite material includes the following steps: mixing PPS resin, modified hexagonal boron nitride, modified composite whiskers, KH560, antioxidant, and lubricant, and then extruding and granulating the mixture in a twin-screw extruder; all other steps are the same.

[0072] Performance testing The PPS composite materials prepared in the above examples and comparative examples were subjected to the following performance tests: 1. Notched impact strength of cantilever beams: GB / T 1843-2008; 2. Tensile properties: GB / T 1040.1-2025, tensile rate is 50 mm / min; 2. Dielectric constant and dielectric loss: GB / T 31838.1-2015, test frequency 10GHz; 3. Thermal conductivity: The thermal conductivity of the composite material was determined using the transient plane method after testing with a Hot Disk TPS thermal conductivity meter.

[0073] Table 1

[0074] Analysis of the data in Table 1 shows that the PPS composite materials prepared using the modified hexagonal boron nitride and modified composite whiskers of the present invention in Examples 1-3 exhibit lower dielectric constant (<3.5) and dielectric loss (<0.003) at a frequency of 10 GHz, while also possessing higher thermal conductivity (thermal conductivity >3.8 W / (m·K)) and mechanical properties (cantilever beam notched impact strength >14 kJ / m). 2 With a tensile strength >150MPa, it solves the technical problems of high thermal conductivity, high dielectric constant, and insufficient toughness of conventional PPS composite materials.

[0075] The modified hexagonal boron nitride in Comparative Example 1 was not grafted with multifunctional epoxy glycidyl ether, and the modified hexagonal boron nitride in Comparative Example 2 was not intercalated with amino-tetraethylene glycol-carboxylic acid. The resulting PPS composite material had significantly increased dielectric constant and dielectric loss, and significantly decreased thermal conductivity. Comparative Example 3 did not modify boron nitride. Although an epoxy-containing silane coupling agent was added, the dielectric constant and dielectric loss of the obtained PPS composite material were still significantly increased, and the thermal conductivity was still significantly decreased. Compared with Examples 1-3, the physical properties of calcium sulfate whiskers in Examples 4-6 were changed, and the mechanical properties, dielectric properties and thermal conductivity of the obtained PPS composite materials were all worse. In Examples 7 and 8, the mass ratio of calcium sulfate whiskers to alumina whiskers was changed, and the resulting PPS composite material could not achieve a balance between mechanical properties and thermal conductivity.

[0076] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A PPS composite material with low dielectric loss and low water absorption, characterized in that, By weight, it includes the following components: 50-70 parts PPS resin, 25-35 parts modified hexagonal boron nitride, 10-20 parts modified composite whiskers, 0.5-2 parts antioxidant, and 0.5-1 part lubricant. The modified hexagonal boron nitride is formed by intercalating hexagonal boron nitride with amino-tetraethylene glycol-carboxylic acid and then grafting multifunctional epoxy glycidyl ether. The modified composite whiskers are calcium sulfate whiskers and alumina whiskers coated with double-terminated amino liquid nitrile rubber.

2. The PPS composite material with low dielectric loss and low water absorption rate according to claim 1, characterized in that, The modified hexagonal boron nitride is prepared by mixing amino-modified hexagonal boron nitride, amino-tetraethylene glycol-carboxylic acid and water, ultrasonically dispersing, heating and stirring, centrifuging, washing and drying to obtain amino-tetraethylene glycol-carboxylic acid intercalated hexagonal boron nitride. The amino-tetraethylene glycol-carboxylic acid intercalated hexagonal boron nitride, multifunctional epoxy glycidyl ether, and ethanol are mixed, heated and stirred, centrifuged, washed, and dried to obtain the final product.

3. The PPS composite material with low dielectric loss and low water absorption rate according to claim 2, characterized in that, The mass ratio of the aminated hexagonal boron nitride, amino-tetraethylene glycol-carboxylic acid, and water is 1:0.7-0.9:40-60; the mass ratio of the amino-tetraethylene glycol-carboxylic acid intercalated hexagonal boron nitride, polyfunctional epoxy glycidyl ether, and ethanol is 10-15:2-3:200-250.

4. The PPS composite material with low dielectric loss and low water absorption rate according to any one of claims 1-3, characterized in that, The modified composite whiskers are prepared by mixing calcium sulfate whiskers, alumina whiskers, double-terminated amino liquid nitrile rubber and acetone, heating and stirring, filtering and drying.

5. The PPS composite material with low dielectric loss and low water absorption rate according to claim 4, characterized in that, The calcium sulfate whiskers are columnar fibers.

6. The PPS composite material with low dielectric loss and low water absorption rate according to claim 5, characterized in that, The calcium sulfate whiskers have a diameter ≤10µm and a length ≤50µm; the alumina whiskers have a diameter ≤1µm and a length ≤10µm.

7. The PPS composite material with low dielectric loss and low water absorption rate according to claim 6, characterized in that, The mass ratio of the calcium sulfate whiskers, alumina whiskers, double-terminated amino liquid nitrile rubber, and acetone is 1:2-4:0.3-0.5:10-15.

8. The PPS composite material with low dielectric loss and low water absorption rate according to claim 7, characterized in that, The number average molecular weight of the double-amino-terminated liquid nitrile rubber is 2000-5000.

9. A method for preparing the low dielectric loss and low water absorption PPS composite material according to any one of claims 1-8, characterized in that, The process includes the following steps: mixing PPS resin, modified hexagonal boron nitride, modified composite whiskers, antioxidants and lubricants, and then extruding and granulating the mixture in a twin-screw extruder.

10. The application of the PPS composite material with dielectric loss and low water absorption as described in any one of claims 1-8 as a substrate material for high-frequency circuits in the field of electronics and electrical appliances.

Citation Information

Patent Citations

  • High thermal conductivity polyphenylene sulfide composite materials, their preparation methods and applications

    CN121045827B

  • A temperature-sensitive reflective heat-insulating coating for the outer wall of an oil storage tank and a preparation method thereof

    CN121108827B

  • Polyphenylene sulfide composite material with low dielectric constant and low dielectric loss as well as preparation method and application thereof

    CN121895760A